Differences in Depressive Symptoms, Perceived Social Support, and Quality of Life among Patients with Hepatitis C and Psychiatric Patients: A Cross-Sectional Study: Quality of Life in Hepatitis C versus Psychiatric Patients - Shahzadi, Mafia; Lakho, Mumtaz; Soomro, Zahid Hussain; Kanhar, Ahmed Ali; Jamal, Iffat; Pervez, Arooba; Rana, Ishrat; Unbrin, Aqila (Pakistan Journal of Health Sciences, 2025)
Hepatitis is a series of viral illnesses that can impact a person’s health and social life. Objective: To investigate the differences in depressive symptoms, perceived social support, and quality of life among the normal population, patients with Hepatitis C, and patients with psychiatric disorders. Methods: 402 participants were taken from Faisalabad’s different urban and rural areas. The participants ’ages ranged from 25 to 54 years. The sample consisted of married participants (n=189, 47%) and unmarried participants (n=213, 53%). A purposive sampling technique was used to collect the data. The following measures were used to assess the findings: Demographic Form, Patient Health Questionnaire, Multidimensional Scale of Perceived Social Support, and World Health Organization Quality of Life-BREF scale. Results: The findings revealed that patients with hepatitis C and patients with psychiatric disorders perceived a high degree of depression as compared to individuals having no history of medical and psychiatric treatment. Similarly, patients with hepatitis C and patients with psychiatric disorders perceived a low degree of social support and quality of life as compared to individuals having no history of medical and psychiatric treatment. Conclusion: In this study, depression, perceived social support, and quality of life were found to significantly differ between the general population, Hepatitis C patients, and people with a mental health condition.